2003
DOI: 10.1128/aem.69.10.6091-6098.2003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nutritional Factors on the Nature, Yield, and Composition of Exopolysaccharides Produced by Gluconacetobacter xylinus I-2281

Abstract: The influence of substrate composition on the yield, nature, and composition of exopolysaccharides (EPS) produced by the food-grade strain Gluconacetobacter xylinus I-2281 was investigated during controlled cultivations on mixed substrates containing acetate and either glucose, sucrose, or fructose. Enzymatic activity analysis and acid hydrolysis revealed that two EPS, gluconacetan and levan, were produced by G. xylinus. In contrast to other acetic acid strains, no exocellulose formation has been measured. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 38 publications
2
47
0
1
Order By: Relevance
“…The results obtained in the present study are in agreement with the general concept expressed in the early studies (15,16) which have reported the highest exopolysaccharides yield using fructose, sucrose, and glucose as carbon sources. Recently, Zhang et al (17), studied the production of gellan exopolysaccharide by growing strains of Sphingomonas paucimobilis QHZJ UJW in the medium containing various carbon sources such as glucose, sucrose, maltose, malt extract powder, and vegetable oil.…”
Section: Discussionsupporting
confidence: 93%
“…The results obtained in the present study are in agreement with the general concept expressed in the early studies (15,16) which have reported the highest exopolysaccharides yield using fructose, sucrose, and glucose as carbon sources. Recently, Zhang et al (17), studied the production of gellan exopolysaccharide by growing strains of Sphingomonas paucimobilis QHZJ UJW in the medium containing various carbon sources such as glucose, sucrose, maltose, malt extract powder, and vegetable oil.…”
Section: Discussionsupporting
confidence: 93%
“…Until now, the production of levan has been reported for other acetic acid bacteria, Acetobacter diazotrophicus 7) and G. xylinus; 4,8) however, there have no reports describing the production of levan in A. bogorensis. It seems that A. bogorensis synthesized levan from sucrose by levansucrase associated with the cell surface.…”
mentioning
confidence: 99%
“…The carbon sources (glucose or lactose), lactic acid and acetic acid in the culture broth were analyzed by HPLC under the following conditions: column, Supelcogel H (300 ·7.8 mm); mobile phase, 0.1 N H 2 SO 4 ; detector, a Waters 410 RI detector; temperature, 30°C [5]. Cell concentration was determined by measuring the optical density at 600 nm (OD 600 ).…”
Section: Methodsmentioning
confidence: 99%